Analisis Skala Ekonomis Kerajinan Ukiran Kayu Lapis Di Kabupaten Badung - Sanjaya, Ida Bagus Putu Windu; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Growth in the industrial sector would have been affected by business scale in the industry that would tend to indicate the level of efficiency. The purpose of this study was to analyze the influence of labor and capital simultaneously and partially to the carving industry of plywood in Badung as well as to analyze the economies of scale and the nature of industrial production of plywood carving in Badung. The population of as many as 539 business units. Samples taken as many as 84 drawn at random by using the formula Slovin. The analysis technique used is multiple linear regression analysis. The analysis showed the labor and capital have a significant effect simultaneously on carving plywood industry in Badung. Variable labor and capital positive effect partially on carving plywood industry in Badung. Economies of scale are carved plywood industry in Badung are in decreasing return of scale. Industrial production of plywood carved in Badung labor intensive.
Keywords: tenaga kerja; modal; produksi industri